2006
DOI: 10.2106/jbjs.e.01313
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc Degeneration: Epidemiology and Genetics

Abstract: Research conducted over the past decade has led to a dramatic shift in the understanding of disc degeneration and its etiology. Previously, heavy physical loading-often associated with occupation-was the main suspected risk factor for disc degeneration, which was commonly viewed as a wear-and-tear phenomenon exacerbated by the precarious nutritional status of the disc. However, results of studies on twins suggest that physical loading specific to occupation and sport plays a relatively minor role in disc degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
237
1
23

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(271 citation statements)
references
References 14 publications
10
237
1
23
Order By: Relevance
“…The fact that after 2 years DT1 did not further increase in the treated levels, but on the contrary significantly decreased in the adjacent disc levels, supports the hypothesis that the initial worsening in previously normal segments was primarily due to the different load distribution generated by the device, and not by a spontaneously evolving discopathy at multiple lumbar levels in these patients because of their possible genetic disposition (36). Also, our results after 2 years confirm the previous observation that dynamic disc stabilization using Dynesys device seems able to lead to tissue regeneration in the more severely degenerated levels, thus improving GAG disc composition, with objective benefits for the patient.…”
Section: Discussionsupporting
confidence: 60%
“…The fact that after 2 years DT1 did not further increase in the treated levels, but on the contrary significantly decreased in the adjacent disc levels, supports the hypothesis that the initial worsening in previously normal segments was primarily due to the different load distribution generated by the device, and not by a spontaneously evolving discopathy at multiple lumbar levels in these patients because of their possible genetic disposition (36). Also, our results after 2 years confirm the previous observation that dynamic disc stabilization using Dynesys device seems able to lead to tissue regeneration in the more severely degenerated levels, thus improving GAG disc composition, with objective benefits for the patient.…”
Section: Discussionsupporting
confidence: 60%
“…Results of exposure-discordant monozygotic and classic twin studies suggest that mechanical factors play a very limited role in segmental spinal degeneration, while constitutional factors and heredity may have a dominant role, explaining 74% of the variance in the adult population studied to date [9]. In vitro studies have found altered biomechanics in the mobile segments adjacent to fusion, including increased mobility and increased intradiscal pressure [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that both genetics and mechanics play a role. Previous studies have shown that genetically determined natural progression of degeneration might be modified to some degree by environmental factors [9]. ASD is likely a consequence of normal degenerative progression influenced by altered biomechanics related to fusion [1,2,4,6,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Validated data for ADD specifically are not available, but prevalence figures for disc degeneration vary from 3 to 56%, with studies of patients with an average age of B21 years reporting a prevalence of up to 24%. The absence of standardized case definitions of disc degeneration hampers comparisons and interpretations of epidemiologic studies of disc degeneration [14]. Gender distribution is unclear, with some studies describing males being more commonly affected, while others report that both sexes are affected equally [14].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of standardized case definitions of disc degeneration hampers comparisons and interpretations of epidemiologic studies of disc degeneration [14]. Gender distribution is unclear, with some studies describing males being more commonly affected, while others report that both sexes are affected equally [14].…”
Section: Introductionmentioning
confidence: 99%